Rapid Synthesis of 3D Porous Nitrogen-Doped Carbon Nanospheres (N-CNSs) and Carbon Nanoboxes (CNBs) for Supercapacitor Electrodes. Issue 5 (28th March 2018) - Zhou, Xing-hai; Cao, Lei; Li, Zhen-huan; Zhang, Ma-liang; Kang, Wei-min; Cheng, Bo-wen
Abstract : In this paper, the porous nitrogen-doped carbon nanospheres (N-CNSs) and carbon nanoboxes (CNBs) with high electrical conductivities of 244 and 329 S . cm −1 and large surface area of 558 and 306 m 2. g −1 are prepared by magnesium (Mg) triggered self-propagating high-temperature synthesis (SHS) using urea and fructose as precursors. Differing from traditional time-consuming calcination technique, the obtained samples are composed of porous and 3D structure with particle size of a few tens of nanometer. Such unique structure can lead to short diffusion paths of ions, abundant active sites for charge-transfer reactions and reasonable electrical/ionic conductivity. The rapid prepared and novel structure of N-CNSs and CNBs electrodes offer a satisfactory specific capacitance (124 and 84 F . g −1 at 0.5 A . g −1 ), good rate performance (103 and 71 F . g −1 at 10 A . g −1 ), and excellent cycling stability (96.2% and 98.6% after 8000 cycles). Most importantly, N-CNSs provides larger surface area and as much as 5.67 wt% of nitrogen incorporation, due to its high content of nitrogen in urea precursors. Thus, it presents higher specific capacitance of 47.6% than CNBs. Therefore, such particularly designed 3D porous carbon provides a promising strategy to ameliorate electrode materials for advanced energy storage systems.